Secondary Principals’ Perceptions of Grading and Grade Reporting Practices - Akins, Jeremie (Southwest Baptist University, 2016)
Effective grading practices in the classroom as well as reporting practices such as standards-based grading (SBG) is one way to report learning (Marzano, 2010). The focus of this particular study was to address alternative ways to tackle the issue of grading and grade reporting in comparison to the traditional grading methods. Specifically, this study explored the perceptions of lead high school principals regarding effective grading, traditional grading, and leadership implementation of grading and grade reporting. In order to provide a successful research platform the development of a reliable and valid survey instrument was conducted. The pilot version of the instrument was completed in various settings to gather results commendable of making predictions and descriptive statements that emphasized the educational public and the sample population. Revisions were necessary after seeing the results from the pilot survey and a final survey was distributed for principal’s perceptions. The sample population consisted of lead principals in approximately 700 high schools within the entire state of Missouri. Respondents were overall favorable to all three scales on the survey— (1) perceptions of grading and grade reporting, (2) leadership of grading and grade reporting, and (3) perceptions of traditional grading and grade reporting. There were a number of statistically significant differences; however, the results suggested that schools are someone open to better grading and grade reporting implementation. It seems apparent, according to the survey results, that some schools have the primary platform or at the very least, desire to make grading changes. Further study is recommended on how to proceed from mere knowledge to application in the secondary setting. Many elementary and some middle schools are moving toward standards-based grading, but high schools seem to be primarily traditional. Another avenue this study could take would be to evaluate the perceptions of students and the effect of different grading practices, especially at the high school level.